Achieving Zero Poverty Goal in Bojonegoro Through the Welfare Sheep Program: Public Value Perspective - Alfiatur Rohmah; Ana Kumalasari; Ida Swasanti; Ousman Corr (Dinasti Research, 2025)
The main objectives of this study are to evaluate the public value of the Welfare Sheep Program in achieving zero poverty in Bojonegoro Regency. This program is one of the efforts made by the Government to improve the welfare of the poor as a form of responsibility and concern from the Government to reduce poverty rates. This study adopts a qualitative method with a case study approach. This type of research is qualitative descriptive. Data collection was carried out through observation, interview, and documentation techniques. The researcher applies Mark Moore's theory of public value, namely Legitimacy and Support, Operational Capability, and Substantial Value. The findings of the study show that the Welfare Sheep program has succeeded in increasing the income of beneficiary families in the form of increasing the number of sheep. However, the availability of quality feed is still the main obstacle to the program's sustainability because of sheep deaths. This happens because no technology can increase livestock productivity through feed. By using modern technology, the feed management process becomes faster, more effective, efficient, and can help meet the nutritional needs of sheep in real-time and allows farmers to produce more nutritious feed that is in accordance with the nutritional needs of sheep.